2019
DOI: 10.1186/s12877-019-1366-x
|View full text |Cite
|
Sign up to set email alerts
|

Use it or lose it: a qualitative study of the maintenance of physical activity in older adults

Abstract: BackgroundLack of physical activity (PA) is a recognised global public health problem, which is increasing in prevalence with a detrimental impact on the pattern of disease worldwide. In the UK, older adults comprise the most sedentary group, with only 57% of males and 52% of females aged 65–74 years and 43% of males and 21% of females aged 75–84 years meeting PA recommendations.PA confers multiple health benefits including increased stamina, muscle, bone and joint strength, increased independence and reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
0
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 60 publications
7
60
0
15
Order By: Relevance
“…Physical and functional impairments [22] and living alone are associated with ability to get up after a fall [23]; only one staff participant highlighted that time and exercise training may be required to get people to the point of having the physical ability to get up, yet the benefits of maintaining activity for older people is recognised and has similar barriers to those we identified. In common with the recent study by Maula and colleagues (2019) [24], we also found that novel use of technology, in the form of on-line information, was used within our sample, applied in such a way that ongoing knowledge and behaviour was changed after accessing on-line guidance.…”
Section: Comparison With Existing Literaturesupporting
confidence: 87%
“…Physical and functional impairments [22] and living alone are associated with ability to get up after a fall [23]; only one staff participant highlighted that time and exercise training may be required to get people to the point of having the physical ability to get up, yet the benefits of maintaining activity for older people is recognised and has similar barriers to those we identified. In common with the recent study by Maula and colleagues (2019) [24], we also found that novel use of technology, in the form of on-line information, was used within our sample, applied in such a way that ongoing knowledge and behaviour was changed after accessing on-line guidance.…”
Section: Comparison With Existing Literaturesupporting
confidence: 87%
“…Importantly, though, given the cross-sectional nature of these data, such associations could reflect reverse or bi-directional causation in that more intact physical function is needed for many types of MVPA. In addition, even if such associations reflected causal relationships, differences in activity of that size are likely unrealistic as a basis for potential intervention targets in older adults due to the magnitude of behavior change required (e.g., increasing daily steps from 3000/day to nearly 9000/day or increasing daily MVPA from 15 min/day to at least 90 min/day) and the existing diversity in older adults’ functional exercise capacity and willingness to routinely engage in this much activity [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current literature examining physical activity, sedentary behavior, and health in older adults suggests that higher levels of moderate-to-vigorous intensity physical activity (MVPA) are key to prolonged health and function [ 2 ]. However, among older adults, for whom physical function typically declines with age [ 3 , 4 ], increasing MVPA may not be feasible due to existing limitations in functional exercise capacity [ 5 , 6 ]. Consequently, public health messages and interventions centered on boosting MVPA in this population may not be effective, optimal, or feasible [ 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, as the elderly have trouble continuing exercise because of physical and environmental restraints, it is very important to motivate them to continue to exercise and stay focused with purpose [11]. Therefore, it is necessary to introduce exercise contents in various ways for them to continue to exercise.…”
Section: Introductionmentioning
confidence: 99%